Effects of Isoflavone Supplementation on the Response to Medroxyprogesterone in Premenopausal Women with Nonatypical Endometrial Hyperplasia: A Randomized, Double-Blind, Placebo-Controlled Trial - Vahedpour, Zahra; Boroumand, Homa; Tabatabaee Anaraki, Shirin; Tabasi, Zohre; Motedayyen, Hossein; Akbari, Hossein; Raygan, Fariba; Ostadmohammadi, Vahidreza (International journal of clinical practice (Esher), 2022)
Objective. The purpose of this study was to evaluate the impact of isoflavone supplementation compared with placebo on endometrial histology and serum estradiol levels in premenopausal women with nonatypical endometrial hyperplasia. Materials and Methods. The present double-blindplacebo-controlled clinical trial was conducted on 100 women with nonatypical endometrial hyperplasia in the age range of 30 to 45 years. Participants were randomly assigned to receive 50 mg of isoflavone (n = 50) or placebos (n = 50) daily for three months. Both groups received the standard treatment of nonatypical endometrial hyperplasia. Endometrial biopsy and blood samples were taken at the baseline and three months after the intervention. The incidence of drug side effects was assessed as well. Results. After three months, 88.4% of isoflavone-administered subjects had a significant histological improvement compared to 68.9% subjects in the placebo group (P=0.02). There were no significant differences between the two groups in the changes of serum estradiol levels and the incidence of drug side effects. Conclusion. The findings of the present study demonstrated that the coadministration of 50 mg of isoflavones and medroxyprogesterone acetate increases the treatment efficacy in women with nonatypical endometrial hyperplasia. Clinical Trial Registration. This trial was registered on the Iranian website for clinical trial registration (https://www.irct.ir/trial/53553).